International Students from Asia in Canadian Universities Institutional Challenges at the Intersection of Internationalization, Racialization and Inclusion - Kim, Ann; Buckner, Elizabeth; Montsion, Jean Michel (Routledge Studies in Global Student Mobility, 2024)
This book explores how the recruitment and retention of Asian international students in Canadian universities intersects with other institutional priorities. Responding to the growing need for new insights and perspectives on the institutional mechanisms adopted by Canadian universities to support Asian international students in their academic and social integration to university life, it crucially examines the challenges at the intersection of two institutional priorities: internationalization and anti-racism. This is especially important for the Asian international student group, who are known to experience invisible forms of discrimination and differential treatment in Canadian post-secondary education institutions. The authors present new conceptualisations and theoretical perspectives on topics including international students' experiences and understandings of race and racism, comparisons with domestic students and/or non-Asian students, institutional discourse and narratives on Asian international students, comparison with other university priorities, cross-national comparisons, best practices, and recent developments linked to the COVID-19 pandemic. Foregrounding the institutional strategies of Canadian universities, as opposed to student experience exclusively, this direct examination of institutional responses and initiatives draws out similarities and differences across the country, compares them within the broader array of university priorities, and ultimately offers the opportunity for Canadian universities to learn from each other in improving the integration of Asian international students and others to their student body. It will appeal to teacher-scholars, researchers and educators with interested in higher education, international education and race and ethnic studies.